2015
DOI: 10.1177/1099800415592175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Topical Insulin on Second-Degree Burns in Diabetic Rats

Abstract: The healing process is complex in diabetic wounds, and the healing mechanism of burn wounds is different from that of incisional or excisional wounds. Data from our previous study indicated that topical insulin cream reduced wound closure time in diabetic rats. Our aim was to investigate the effect of topical insulin cream on wound healing following second-degree burns in control and diabetic rats. Rats were divided into four groups: control (nondiabetic) rats treated with placebo (CP), control (nondiabetic) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
46
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 38 publications
1
46
0
3
Order By: Relevance
“…More recently topical application of insulin has been shown to accelerate healing of diabetic ulcers; however, its mechanism was not fully understood. Although effect of insulin was ascribed to its glucose control properties, later studies revealed different mechanisms through which insulin improves wound healing . In our study using systemic insulin therapy was associated with higher rates of complete wound healing even after adjusting for multiple confounding covariate, including blood glucose control.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…More recently topical application of insulin has been shown to accelerate healing of diabetic ulcers; however, its mechanism was not fully understood. Although effect of insulin was ascribed to its glucose control properties, later studies revealed different mechanisms through which insulin improves wound healing . In our study using systemic insulin therapy was associated with higher rates of complete wound healing even after adjusting for multiple confounding covariate, including blood glucose control.…”
Section: Discussionmentioning
confidence: 43%
“…Although effect of insulin was ascribed to its glucose control properties, 12 later studies revealed different mechanisms through which insulin improves wound healing. 13,14 In our study using systemic insulin therapy was associated with higher rates of complete wound healing even after adjusting for multiple confounding covariate, including blood glucose control. The independent association of insulin therapy with higher rates of complete wound healing contends mechanisms other than blood glucose control for insulin.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The wound healing disorder in diabetes can be attributed to various factors, such as weak blood supply, reduced proliferative potential and low infl ammatory changes [16] . Some burn, surgical incision or diabetic wound animal studies were demonstrated that inadequate or non-healing wounds can be treated with topical insulin application [17][18][19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…The problem of how to continually release insulin in an effective manner to promote the growth of granulation tissue and wound healing is a known concern (9). Previous findings have shown that local infiltration injections increase the absorption efficiency of insulin while exerting little influence on blood sugar contents (10). The possibility that insulin may promote wound healing following simple deep burn skin flap transplantation in humans and its possible mechanism were analyzed in this clinical case-control study.…”
Section: Discussionmentioning
confidence: 99%